Content Vol. 42 No. 2 (2021) - Editorial, Coordinador (Revista Mexicana de Ingenieria Biomedica, 2021)
E-book edition of the volume 42, number 2, year 2021, of the Revista Mexicana de Ingeniería Biomédica. In this issue: Determination of early bone metastasis on Bone Scans Using the Gray Levels Histogram Theoretical Study of the Function of the IP3 Receptor / BK Channel Complex in a Single NeuronAntibacterial Activity Analysis of Hydroxyapatite Based Materials with Fluorine and Silver Three-dimensional printing in healthcare Biomechanical Evaluation of Hemiarthroplasty in the First Proximal Phalanx. A Finite Element Study Detection of Exudates and Microaneurysms in the Retina by Segmentation in Fundus Images Feature Extraction from Distributions of Phase Synchronization Values of EEG Recordings Efficacy of Virtual Reality in Neurorehabilitation of Spinal Cord Injury Patients: A Systematic Review Numerical Simulation of a Physiological Mathematical Model of Energy Consumption in a Sarcomere Development of Films, Based on Oxidized Ipomea Batatas Starch, with Protein Encapsulation Pressure Pain Threshold Values Obtained Through Algometers Evaluation of Parameters in PLA and PCL Scaffolds to be Used in Cartilaginous Tissues Autonomic Face Mask Detection with Deep Learning: an IoT Application